Who is knowledgeable, is strong : science, class, and the formation of modern Iranian society, 1900-1950 - Schayegh, Cyrus (University of California Press, 2009)
In this book, Cyrus Schayegh tells two intertwined stories: how in early 20th-century Iran, an emerging middle class used modern scientific knowledge as its cultural & economic capital, & how along with the state, it employed biomedical sciences to tackle modern problems like the increasing stress of everyday life.